Control of pulsed beam parameters at the exit channel of the high-intensity linac - Vereshchaka, V.N.; Dovbnya, A.N.; Dronov, R.N.; Myakushko, L.K.; Reprintsev, L.V.; Savchenko, A.N.; Sarvilov, A.A.; Tatanov, V.I.; Shevchenko, V.A.; Shendrik, V.A.; Boriskin, V.N. (Вопросы атомной науки и техники, 2014)
Control of beam parameters is important for maintenance of linac operating conditions, as well as, for securing a high-speed protection of exit channel components against the beam damage. For this purpose the beam current, beam center position and ellipse cross-section (10 MeV, 10 kW, 1 А/pulse, 300 Hz, 3.5 μs) are measured at the output part of linac. Two similar current sensors, position sensor and water-cooled copper collimator in the gap between the current sensors were used. All the sensors of a magnetic induction type have windings on ferrite coils placed in vacuum. The system is described and the component calibration results are reported. The coefficient of beam losses during the transit through the collimator is calculated with the use of a special microprocessor placed in the ADC module which receives the signal from two current sensors. An algorithm of signal digitization eliminates the failures under the action of pulse interference. When the set threshold of beam losses is exceeded, the signal from the electron source blocking enters into the linac synchronization unit. Control of position sensor signals is carried out without beam chopping by the on-line comparison between the four position sensor signals and the current sensor signal being placed in the same case. The data on the beam parameters are displayed on the PC screen. The system is successfully used during several years.